MOTIVASI MENGAJAR GURU DITINJAU DARI KEPUASAN KEBUTUHAN BERDASAR DETERMINASI DIRI - Utomo, Hanggara Budi; Suminar, Dewi Retno; Hamidah, Hamidah; Yulianto, Dema (Faculty of Psychology, Diponegoro University, 2019)
This study specifically aims to analyze the contribution of need satisfaction for autonomy, need satisfaction for competence, and need satisfaction for relatedness that is associated with teacher teaching motivation. The participants of this study were 84 early childhood education programs teachers in Kediri Regency and Tulungagung Regency (100% women, Mage = 31.71 years; SD = 8.86). Data were collected using the Basic Need Satisfaction in General Scale and the Autonomous Motivation for Teaching Questionnaire presented in Indonesian language. Data analysis in this study used descriptive statistical techniques and Pearson correlation technique. The results shows that there is no significant correlation between need satisfaction for autonomy with teaching motivation (r= .043; p = .585), there is significant correlation between need satisfaction for relatedness with teaching motivation (r= .208; p = .008), and there is significant correlation between need satisfaction for competence with teaching motivation (r= .167; p = .031). Understanding teaching motivation based on self-determination may help teachers in disadvantaged areas to improve and recognize self-potential, so that teachers can develop themselves by optimizing need satisfaction as a factor that influences the teacher's activities in teaching.